Analisis Efektivitas dan Kontribusi Penerimaan Pajak Parkir terhadap Pendapatan Asli Daerah Kota Samarinda - Krisna Pashaputra; Aji Sofyan Effendi; Juliansyah Roy (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The main objective of this study was to analyze or determine the effectiveness and contribution of Revenue Revenue Against Parking Urban Samarinda in 2011- 2015. The  method  used  is  descriptive  analysis  and  research  at  the  Regional Revenue Office Samarinda and data used are secondary data. This study uses data Regional Revenue Samarinda 2011-2015. The results showed that the year 2013 has a low effectiveness criteria of (81.94%) and in 2011 had the highest effectiveness criteria of (103.58%), as well as for contributions in 2014 had the smallest contribution criteria of (0, 82%) and 2015 has contributed the highest criteria of (1.49%). Based on the calculation and analysis of the effectiveness of these contributions should Samarinda Regional Revenue Office did improve and trying to manage a good parking tax to increase revenue from local taxes.Keywords: Effectiveness, Contribution, parking tax and local revenues